A Gender Mainstreaming Approach of Social and Economic Impact Management during the Covid-19 Pandemic in Urban Settlements - Esariti Landung (EDP Sciences, 2021)
This article describes the gender mainstreaming based community approach in Polaman Village, Mijen District in reducing the risk of non-natural disasters for the Covid-19 pandemic. This study used the quantitative approach and data collection technique by interviewing 3 community representatives and distributing questionnaires to 24 households. Assessment of gender mainstreaming indicators used the scoring analysis with 5 indicators, i.e., access, benefits, participation, control and inclusion. The results showed that Kampung Siaga Candi Hebat was formed through the establishment of a food storehouse to help meet the needs of food security during the pandemic, freshwater cultivation through involving people affected by layoffs, and the construction of a health center as a monitoring facility, and an isolation accommodation for residents affected by the Covid-19 virus. However, in the management of residential spaces, impediments were still found in terms of lack of availability and management of existing green public spaces and the lack of management integration of waterways, water disposal and garbage. In conclusion, the control aspect was found to be the most influential, with a contribution value of 21% out of 75%. Accordingly, accustomization of the gender mainstreaming approach showed a value of 75% which can be considered quite effective.